PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA - Rina Mudjiyanti; Salis Saevy Maulani (Media Ekonomi, 2017)
The study aims to examine the effect of liquidity and profitability towards the disclosure of corporate social responsibility (CSR). The Independent variable used in this research were liquidity and profitability, while the dependent variable was corporate social responsibility (CSR). Population in this study were manufacturer companies in the consumption goods sector listed in the Indonesian Stock Exchange for the period 2013-2015. The samples in this study were selected by using purposive sampling method and obtained as many 67 observation samples. The analysis technique used in this research was multiple linier regression analysis. The result of the analysis proved that the liquidity variable has negatively affect the corporate social responsibility with a significance value of 0,024. Variable profitability has positive affect the corporate social responsibility with a significance value of 0,005. Keywords : Corporate social responsibility, Liquidity, Profitability